PENGARUH PROFITABILITAS, LEVERAGE, DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR DI BEI - Wijaya, Michael; Setijaningsih, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2025)
This study aims to analyze the effect of profitability, leverage, and firm size on the firm value of infrastructure companies listed on the Indonesia Stock Exchange (IDX). The sample methodology utilized in this study was purposive sampling. The sample was 19 infrastructure companies in the study period from 2020 to 2022, resulting in a total of 57 data processed. The data were processed using SPSS 25 software. The result showed that profitability and firm size positively affect firm value. On the other hand, leverage negatively affects firm value.